Cutaneous Na+ storage strengthens the antimicrobial barrier function of the skin and boosts macrophage-driven host defense - Jantsch, Jonathan Antti Michael; Neuhofer, Wolfgang (Cell metabolism, 2015)
Immune cells regulate a hypertonic microenvironment in the skin; however, the biological advantage of increased skin Na+ concentrations is unknown. We found that Na+ accumulated at the site of bacterial skin infections in humans and in mice. We used the protozoan parasite Leishmania major as a model of skin-prone macrophage infection to test the hypothesis that skin-Na+ storage facilitates antimicrobial host defense. Activation of macrophages in the presence of high NaCl concentrations modified epigenetic markers and enhanced p38 mitogen-activated protein kinase (p38/MAPK)-dependent nuclear factor of activated T cells 5 (NFAT5) activation. This high-salt response resulted in elevated type-2 nitric oxide synthase (Nos2)-dependent NO production and improved Leishmania major control. Finally, we found that increasing Na+ content in the skin by a high-salt diet boosted activation of macrophages in a Nfat5-dependent manner and promoted cutaneous antimicrobial defense. We suggest that the hypertonic microenvironment could serve as a barrier to infection.
Gesehen am 05.10.2017
Im Titel ist "+" hochgestellt